Design of a Marine Weather Monitoring System Based on an Arduino System - Rahmat, M. Basuki; Widodo, Hendro Agus; Khumaidi, Agus; Budiawati, Ratna; Mudjanarko, Sri Wiwoho (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2024)
The need for information about weather conditions in a particular environment is very necessary for the community, so that they can plan activities for the future. A forecaster cannot process data to predict weather or climate conditions if it is not accompanied by historical data within a predetermined time period. Data is a very important savings for future generations, because data will make the nation's generation smart. Without data, all previous information would not be known to be studied. The current condition of the earth is very worrying and not easy to predict. Therefore, it is very important to have integrated observations and services in coastal and marine areas to support resilience to climate change and other marine hazards.Sustainable marine observations and services are very important and relevant to reduce potential problems and threats arising from climate change.In this paper we will discuss the creation of a tool for monitoring weather, where this tool will take data on humidity, temperature and rainfall. so that from this data we can predict weather conditions in the area. By using the fuzzy method, the combination of these three data can be used by fishermen to make decisions about whether it is still safe to go to sea.The system is built based on Arduino using muoring buoy media. where this tool will be placed in the sea. The power supply system uses solar cells, so that it can independently meet the power needs of the equipment. From the test results the system can work normally and well.